Pengaruh Edukasi Gizi tentang Pencegahan Hipertensi melalui Media Permainan Kartu terhadap Peningkatan Pengetahuan dan Sikap Remaja di SMAN 1 Krian - Chika Awalia Rachmawati; Rita Ismawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is referred to as “the silent killer”, the World Health Organization (WHO) estimates that 29% of the world's population will experience hypertension in 2025, the potential increase in essential hypertension in adolescents can continue into adulthood due to lifestyle changes. So, it is necessary to provide nutrition education as a prevention of hypertension through the media of card games. The purpose of this study was to determine the effect of nutrition education on the prevention of hypertension through card game media on increasing the knowledge and attitudes of adolescents at SMAN 1 Krian. This type of research is quasi-experimental with Two Group Pre test-Post test Control Group Design. The research sample was 48 adolescents at SMAN 1 Krian, divided into experimental and control groups. Knowledge data with multiple choice knowledge test and attitude from attitude questionnaire using linkert scale. Data analysis of the Wilcoxon test was 0.00 < 0.05 for the increase in knowledge in the control group and the experimental group, while the increase in attitude was 0.00 < 0.05 for the control group and the experimental group. Data analysis using the Mann-Whitney Test (p>0.05), obtained a different test for increasing knowledge (0.22> 0.05), while a different test for increasing attitudes (0.02 < 0.05). The results showed that there was no significant difference in nutrition education on the prevention of hypertension through card game media on improving knowledge, while there was a significant difference in nutrition education on the prevention of hypertension through card game media on improving adolescent attitudes at SMAN 1 Krian.